PENGGUNAAN SARANA NONPENAL DALAM UPAYA PENCEGAHAN PEREDARAN NARKOBA MELALUI PERAIRAN KOTA TANJUNGPINANG - Gilang Nugraha R; Mexsasai Indra; Erdiansyah Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
In the criminal justice system, punishment is not an end in itself and is not the only way to achievecriminal objectives or the purpose of the criminal justice system. The goal to be achieved with a punishmentis to improve the person and the criminal himself and to make people deterred. Judging from the economicalaspect of imprisonment, prison is not really efficient, it should not be applied. So if the penal law criminalpolicy has not been able to provide a deterrent effect for the perpetrators of criminal acts of circulatingnarcotics, it is necessary to apply non-criminal measures.This study is a sociological or empirical research, namely the type of research that usescommunity assumptions in looking for facts that occur in the field to answer an existing problem. Thisresearch was conducted in the jurisdiction of the Riau Prosecutor's Office. While the population and sampleare parties related to the problems examined in this study, the data sources used, primary data, secondarydata, and tertiary data. The technique of collecting data in this study was through interviews and literaturereview.From the results of the study, the authors can conclude, first, the use of nonpenal facilities inefforts to prevent drug trafficking in the Tanjungpinang waters law area is not effective due to the inhibitingfactors in carrying out their duties, especially facilities in the sea or waters so that law enforcement is notoptimal. The obstacles faced by the Bintan Resort Police in the prevention of drug trafficking usingnonpenal facilities are due to their strategic location, the number of rat ports, the vast area of the watersand the lack of personnel from the Bintan Resort Police in carrying out their duties and infrastructure. Theefforts made by the Bintan Resort Police in overcoming barriers to preventing drug trafficking are tocoordinate with Satpolair which has facilities and infrastructure in sea or water lanes.Keywords: Nonpenal Facilities - Circulation of Drugs